Pengaruh Inflasi dan Nilai Tukar (Kurs) Terhadap Pembiayaan Mudharabah Pada Perbankan Syariah di Indonesia - Aas Ariska; Alfi Nihayatul Rohmah; Agus Eko Sujianto (CiDEA Journal, 2023)
Over time, Islamic banking is growing more rapidly, this phenomenon also affects the economic system in Indonesia. This study aims to determine the effect of inflation and exchange rates on mudharabah financing in Islamic banking in Indonesia. This research is a quantitative study using time series data. The data used is secondary data obtained from the official website of Bank Indonesia (BI) and the Central Bureau of Statistics (BPS). The samples used in this study are inflation, exchange rates and mudharabah which are annual historical data starting from 2013-2021. The data analysis technique is using multiple regression analysis with the Ordinary Least Square (OLS) method. This study shows the results that inflation has a significant negative effect on mudharabah financing. Meanwhile, the exchange rate does not have a significant effect on mudharabah financing.